Macrophage inhibitory cytokine‐1 promotes angiogenesis by eliciting the GFRAL‐mediated endothelial cell signaling. Issue 5 (5th November 2020) - Lee, Jaeseob; Jin, Young‐June; Lee, Moon‐Sung; Kim, Young‐Myeong; Lee, Hansoo
Abstract: Macrophage inhibitory cytokine‐1 (MIC‐1) is a cytokine with pleotropic actions and its expression is markedly increased by inflammation and cardiac injury and in cancers. In particular, MIC‐1 production after cardiac ischemia injury is associated with enhanced cardiac angiogenesis as well as myocardial protection. However, it remains uncertain whether MIC‐1 itself has proangiogenic activity. In this study, we tried to determine the precise role of MIC‐1 in physiological and pathological angiogenesis. Human microvessel endothelial cells responded to MIC‐1 with enhanced angiogenic behaviors. Employing various angiogenesis assays, MIC‐1 was found to promote vessel formation and development with a potency similar to that of vascular endothelial growth factor (VEGF). MIC‐1 transgenic (Tg) mice also displayed enhanced neovascularization in both developing embryos and neonatal mouse retinas, compared with wild‐type mice. Furthermore, endothelial cells (ECs) isolated from MIC‐1 Tg mouse lung exhibited higher angiogenic potential than ECs from wild‐type lung. MIC‐1‐induced angiogenesis was also observed in the recovery or healing processes of injuries such as hindlimb ischemia and skin wounds in mice. However, unlike VEGF, MIC‐1 induced neither endothelial inflammation nor increased vascular permeability. In ECs, the MIC‐1 signal exerted proangiogenic actions via the MEK/extracellular signal‐regulated kinase‐ and phosphatidylinositol 3‐kinase/Akt‐dependent pathways. Notably, these MIC‐1 signaling events in ECs were abrogated by small interfering RNA‐mediated knockdown of GFRAL, suggesting that GFRAL is an EC receptor for MIC‐1. In summary, we here show a novel role of MIC‐1 as a potent EC activator, which promotes both normal and injury‐related angiogenesis. Abstract : The present study reveals that macrophage inhibitory cytokine‐1 (MIC‐1) is a novel angiogenic cytokine without proinflammatory activity, along with its angiogenic signaling events in endothelial cells. Of particular note, MIC‐1 seems to play an important role in blood vessel regeneration in pathological lesions caused by injury. Thus, this study not only provides new insights into MIC‐1‐dependent restoration of microvascular homeostasis but also proposes potential beneficial use of MIC‐1 in regenerative medicine.